Reflectance spectroscopy: to shed new light on the capillary refill test. Issue 1 (24th May 2017) - John, Rani Toll; Henricson, Joakim; Nilsson, Gert E; Wilhelms, Daniel; Anderson, Chris D.
Abstract: To use Bioengineering methodology is used to achieve, at five anatomical sites, a detailed, quantitative assessment of the return of blood content to the blanched area, during the Capillary Refill (CR) test. An observational, non‐randomized, experimental study on 23 healthy subjects (14 females) was performed in our climate controlled skin physiology laboratory. Our main outcome measures were based on the chronological assessment and quantification of red blood cell concentration (RBC) after the release of blanching pressure in the CR test, using Tissue Viability Imaging (TiVi), a digital photographic technique based on polarisation spectroscopy. TiVi enabled collection of detailed data on skin RBC concentration during the CR test. The results were shown as curves with skin blood concentration (TiVi‐value) on the y‐axis and the time on the x‐axis. Quantitative CR responses showed site and temperature variability. We also suggest possible objective endpoint values from the capillary refill curve. Detailed data on skin RBC concentration during the CR test is easily obtained and allows objective determination of end points not possible to achieve by naked eye assessment. These findings have the potential to place the utility of the CR test in a clinical setting in a new light.Picture : Regular photograph and TiVi Image showing CR test and corresponding graph for the CR response. Abstract : Polarized reflectance spectroscopy enables quantitative assessment of the return of blood to the blanched area, during the Capillary Refill (CR) test. CR test is currently performed at various body sites normally by naked eye assessment. The reliability and validity of the CR test has been questioned. Quantitative CR responses show site and temperature variability. The availability of objective endpoint values would increase the utility of the CR test.